Prevention of fetal brain injury in category II tracings - Masahiro Nakao; Michael G. Ross; Shoichi Magawa; Satoshi Toyokawa; Kiyotake Ichizuka; Naohiro Kanayama; Shoji Satoh; Nanako Tamiya; Akihito Nakai; Keiya Fujimori; Tsugio Maeda; Akira Oka; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction With category II fetal heart rate tracings, the preferred timing of interventions to prevent fetal hypoxic brain damage while limiting operative interventions remains unclear. We aimed to estimate fetal extracellular base deficit (BDecf) during labor with category II tracings to quantify the timing of potential interventions to prevent severe fetal metabolic acidemia. Material and methods A longitudinal study was conducted using the database of the Recurrence Prevention Committee, Japan Obstetric Compensation System for Cerebral Palsy, including infants with severe cerebral palsy born at ≥34 weeks' gestation between 2009 and 2014. Cases included those presumed to have an intrapartum onset of hypoxic–ischemic insult based on the fetal heart rate pattern evolution from reassuring to an abnormal pattern during delivery, in association with category II tracings marked by recurrent decelerations and an umbilical arterial BDecf ≥ 12 mEq/L. BDecf changes during labor were estimated based on stages of labor and the frequency/severity of fetal heart rate decelerations using the algorithm of Ross and Gala. The times from the onset of recurrent decelerations to BDecf 8 and 12 mEq/L (Decels‐to‐BD8, Decels‐to‐BD12) and to delivery were determined. Cases were divided into two groups (rapid and slow progression) based upon the rate of progression of acidosis from onset of decelerations to BDecf 12 mEq/L, determined by a finite‐mixture model. Results The median Decels‐to‐BD8 (28 vs. 144 min, p < 0.01) and Decels‐to‐BD12 (46 vs. 177 min, p < 0.01) times were significantly shorter in the rapid vs slow progression. In rapid progression cases, physicians' decisions to deliver the fetus occurred at ~BDecf 8 mEq/L, whereas the “decisions” did not occur until BDecf reached 12 mEq/L in slow progression cases. Conclusions Fetal BDecf reached 12 mEq/L within 1 h of recurrent fetal heart rate decelerations in the rapid progression group and within 3 h in the slow progression group. These findings suggest that cases with category II tracings marked by recurrent decelerations (i.e., slow progression) may benefit from operative intervention if persisting for longer than 2 h. In contrast, cases with sudden bradycardia (i.e., rapid progression) represent a challenge to prevent severe acidosis and hypoxic brain injury due to the limited time opportunity for emergent delivery.